Serviceability behavior of High Strength Concrete I-beams reinforced with Carbon Fiber Reinforced Polymer bars (Journal of Engineering, 2013)
Fiber Reinforced Polymer (FRP) bars are anisotropic in nature and have high tensile strength in the fiber direction. The use of High-Strength Concrete (HSC) allows for better use of the high-strength properties of FRP bars. The mechanical properties of FRP bars can yield to large crack widths and deflections. As a result, the design of concrete elements reinforced with FRP materials is often governed by the Serviceability Limit States (SLS). This study investigates the short-term serviceability behavior of FRP RC I-beams. Eight RC I-beams reinforced with carbon-FRP (CFRP) and four steel RC I-beams, for comparison purposes, were tested under two-point loading. Deformations on the concrete and crack widths and spacing are measured and analyzed. A discussion on the main aspects of the SLS of FRP RC is introduced. The service load that fulfills the serviceability requirements, at a cross-section level, ranges between 0.27 and 0.38 times the ultimate load for sections dimensioned to fail in concrete crushing. The determinant criterion is the deflection limitation